2005
DOI: 10.1038/sj.ejcn.1602174
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition communication styles of family doctors: results of quantitative research

Abstract: Objective: To assess the nutrition communication styles of Dutch family doctors and in particular to assess its psychosocial and sociodemographic correlates. Design: A cross-sectional study in which a representative sample of 600 Dutch family doctors completed a questionnaire. Setting: The survey was conducted in October and November 2004 in the Netherlands. Subjects: A total of 267 family doctors completed the questionnaire (response rate 45%). Methods: Principal component factor analyses with varimax rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 23 publications
(32 reference statements)
1
32
1
Order By: Relevance
“…Our finding is in agreement with Guo et al (17) . However, it contrasts with other studies, in which task perception appeared to be the best predictor (13,18,21) . Nevertheless, task perception added to the explained variance in those other studies on prediction.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding is in agreement with Guo et al (17) . However, it contrasts with other studies, in which task perception appeared to be the best predictor (13,18,21) . Nevertheless, task perception added to the explained variance in those other studies on prediction.…”
Section: Discussioncontrasting
confidence: 99%
“…The title of the fourth Heelsum workshop (2004) (64,(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96) showed that we were aware that empowering and support were needed for both family doctors and patients. The disease-based evidence in primary care, the individual strategy of change, and the population interface of primary care were central themes in this workshop.…”
Section: International Workhops Of the Heelsum Collaboration On Nutrmentioning
confidence: 99%
“…The doctor has the medical knowledge, patients know their food habits and beliefs. We discussed the role of empowerment in making healthy choices easy choices (87); public health impact of community-based nutrition and lifestyle interventions (88); influencing patients` nutrition patterns through communication (89); potentials and pitfalls for nutrition counselling in general practice (90); the role of social support in lifestyle-focused weight management interventions (91); PCPs`different communication styles (92), and the rarity of reported nutritional deficiency in general practice (97).…”
Section: International Workhops Of the Heelsum Collaboration On Nutrmentioning
confidence: 99%
See 1 more Smart Citation
“…For each topic, we will provide a chronological overview, starting with the oldest study and ending with the latest. In most cases, these are results of our own empirical studies regarding nutrition communication between GPs and patients [17][18][19][20][21]. All authors were namely participants of a project called "Nutrition education through health professionals".…”
Section: Introductionmentioning
confidence: 97%